Fluorination Homologation of Biorenewable Synthon Cyrene - Johannes Puschnig; Ben W. Greatrex (Molbank)
A one-carbon difluorocyclopropanation/ring-expansion has been developed for the chiral synthon Cyrene, which is obtained via cellulose pyrolysis. The ring-enlargement was achieved by converting Cyrene (dihydrolevoglucosenone) into an enamine, reacting it with an in situ-generated difluorocarbene, and then heating it to ring-open the cyclopropane. Access to the product provides access to fluorinated analogues of this valuable chiral biomass derivative.